Productivity and water-use efficiency of linseed (Linum usitatissimum L.)-based cropping systems as influenced by integrated nutrient management under rainfed condition - VERMA, AMAR KANT; YADAV, P N (Journal of Soil and Water Conservation, 2018)
A field experiment was carried out at Kanpur during rabi seasons of 2015-16 and 2016-17. The experiment consisted of nine cropping systems viz. C1: Linseed sole, C2: Lentil sole, C3: Barley sole, C4: Linseed + lentil (3:1), C5: Linseed + barley (3:1), C6: Linseed + lentil (4:1), C7: Linseed + barley (4:1), C8: Linseed + lentil (5:1) and C9: Linseed + barley (5:1), and three integrated nutrient management options viz. N1: RDN, N2: 75% RDN through inorganic + 25% RDN through vermicompost N3: 75% RDN through inorganic + 25% RDN through vermicompost + bio-fertilizer (seed coating) + PSB @ 2.5 kg ha-1 in soil. The experiment was conducted in a three-time replicated split-plot design keeping cropping systems in main-plots and INM in sub-plots. The results clearly reveals that seed, stover/or straw yields of linseed, lentil and barley was influenced significantly in sole cropping as compared to intercropped treatments. Amongst the cropping system the maximum seed and stover yield was obtained in linseed + lentil (3:1) and linseed + barley (3:1) during the two different years. The use of integrated nutrient management further exhibited the significance over RDN. Linseed equivalent yield was highest (13.33 & 12.11 q ha-1) in the treatment of linseed + lentil (3:1) during 2015-16 & 2016-17, respectively. The application of INM further showed significance and use of 75% RDN through inorganic + 25% RDN through vermicompost + bio-fertilizer (seed coating) + PSB @ 2.5 kg ha-1 in soil exhibited significantly higher values during the years of study. Maximum water-use was found in relevant sole crops of linseed, lentil and barley whereas highest WUE of 6.15 & 5.44 kg ha-1 mm-1 was observed in the treatment of linseed + lentil (3:1). The corresponding lowest values of 2.24 & 1.97 kg ha-1 mm-1 were observed in the treatment of barley sole during the two different years.